2019
DOI: 10.3928/23258160-20190129-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Abicipar Pegol (an Anti-VEGF DARPin Therapeutic) in Patients With Neovascular Age-Related Macular Degeneration: Studies in Japan and the United States

Abstract: BACKGROUND AND OBJECTIVE: To evaluate comparability of abicipar pegol (abicipar) effects in patients with treatment-naïve neovascular age-related macular degeneration (nAMD) in Japan and the United States. PATIENTS AND METHODS: Phase 2, multicenter, randomized, double-masked, 20-week studies (BAMBOO, Japan; CYPRESS, United States). Patients (n = 25 each study) received three monthly intravitreal injections of abicipar 1 mg or 2 mg or five monthly intravitreal injections of ranibizumab 0.5 mg. RESULTS: Mean bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Noninfectious inflammation was reported after anti-VEGF injections 34 . Although the incidence was very low, most anti-VEGF agents have caused inflammation after intravitreal injections 36 38 . Complement dysregulation may be a predisposing factor after the anti-VEGF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Noninfectious inflammation was reported after anti-VEGF injections 34 . Although the incidence was very low, most anti-VEGF agents have caused inflammation after intravitreal injections 36 38 . Complement dysregulation may be a predisposing factor after the anti-VEGF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Noninfectious in ammation was reported after anti-VEGF injections 37 . Although the incidence was very low, most anti-VEGF agents have caused in ammation after intravitreal injections [38][39][40] . The complement dysregulation may be one of predisposing factors after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Results of three phase 2 studies of abicipar in patients with treatment-naïve nAMD suggested a potential for abicipar 2 mg to improve or maintain vision in patients with quarterly dosing. 12,13 J o u r n a l P r e -p r o o f Subsequently, two 2-year phase clinical trials (CEDAR and SEQUOIA) with identical protocols compared abicipar 2 mg every 8 or 12 weeks after initial doses (Q8 or Q12) to ranibizumab 0.5 mg every 4 weeks (Q4) in patients with treatment-naïve nAMD. We recently reported the pooled phase 3 study results through 1 year.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%